The Influence of Leverage, Sales Growth, Activity Ratio, and Liquidity on Profit Growth Which is Moderated by Firm Size in Health Sector Companies Listed on the Indonesian Stock Exchange During the 2019 – 2023 Period - Wahyu Heri Prasetyo; Billy Josef Anis; Sunita Dasman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research was carried out to test and prove empirically the influence of leverage, sales growth, activity ratio, and liquidity on profit growth which is moderated by firm size. The sample in this research is 15 health sector companies listed on the IDX during the 2019 - 2023 period. This research uses the SEM research method with the Smart PLS application analysis tool. The type of data used by researchers is secondary data in the form of company financial report data. The data used by the research is panel data. Panel data is a combination of time series data and cross-section data. The cross-section data used in this research is 15 companies. Meanwhile, the time series data is from Q1 2019 to Q4 2023. The results of this research are that leverage, sales growth, activity ratio, and liquidity do not affect profit growth. Firm size is unable to moderate the influence of leverage and activity ratio on profit growth. However, Firm Size weakens the influence of sales growth on profit growth. The bigger a company, the weaker or smaller the influence of sales growth on profit growth. The results of this research indicate that firm size can strengthen the influence of liquidity on profit growth. With high liquidity and large company size, the company has a high probability of paying off its debts easily. Apart from that, large companies also have many ideas and experiences in their business, which can support profit generation.